Enhancing mental toughness in student-athletes during the COVID-19 pandemic via educational-based psychological skills training: Preliminary results of a pilot study - Giuliani, M. L.; Morgan, G. B.; Cowden, R. B.; Forsse, J. S.; Stamatis, A. (International Journal of Exercise Science Conference Proceedings, 2021)
One group of measures against the COVID-19 pandemic have been the non-pharmaceutical interventions (NPIs). NPIs taken by the NCAA included suspension of athletic seasons. Suspended championships during the pandemic have led to changes in athletic role identity and social connectedness, which negatively affected student-athletes` mental health (MH). One psychological characteristic that has the potential to support the well-being of athletes is mental toughness (MT). MT is associated with successful sport performance and positive MH outcomes. Although empirical evidence supports the effectiveness of educational-based psychological skills training (PST) in promoting MH, similar effects might be found for an educational-based PST that is centered on MT. PURPOSE: To examine if educational-based PST structured around MT can support the MH of student-athletes whose season has been suspended due to COVID-19. METHODS: Six seminars have been designed as part of the "Wellness Series" at a NCAA institution that typically competes in the SUNYAC conference. The first two sessions have been conducted so far. The first seminar included educational information about PST in Sports Psychology and MT in sport. In total, 63 student-athletes were self-assessed using the Mental Health Continuum-Short Form and the Mental Toughness Index (MTI) before and after. The second seminar included educational information about Optimistic Style (OS) and Emotion Regulation (ER). In total, 48 participants rated their knowledge of OS and ER (range: 1-7) and answered the corresponding MTI items before and after. RESULTS: First session: The correlation between MT and MH scores before was r = 0.25 (p = 0.003). It increased to r = 0.46 (p = 0.0006) immediately afterwards. Second session: There was a significant difference in the scores of: a) OS Knowledge before (M=3.52, SD=1.74) and OS Knowledge after (M=5.72, SD=0.94); t(75)= 6.2679, d = 1.51, p < 0.0001; b) ER Knowledge before (M=3.81, SD=1.75) and ER Knowledge after (M=5.76, SD=1.05); t(75)= 5.4307, d = 1.28, p < 0.0001; and c) ERMTI before (M=4.77, SD=1.15) and ERMTI after (M=5.45, SD=0.93); t(74)= 2.6861, d = 0.63, p = 0.0089, but not in OSMTI before (M=5.32, SD=1.19) and OSMTI after (M=5.69, SD=0.95); t(74)= 1.4176, d = 0.33, p = 0.1605. CONCLUSION: The MT-MH relationship appears stronger. Athletes perceived their post-intervention level of knowledge of OS and ER as higher. Their postintervention self-reported MTI scores in OS and ER were higher. This preliminary evidence supports the continuation of data collection. The long-term effects of NPIs are not clear. Our research may be important in terms of US collegiate policies concerning PST support of student-athletes during and post-COVID-19.